THE MOST IMPORTANT REQUIREMENTS THAT ENSURE EFFECTIVE PEDAGOGICAL CONTROL OF STUDENTS' SELF-EDUCATIONAL ACTIVITIES - Iminakhunova, Iroda (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Designing the process of self-education must be attributed, first of all, to the management of self-education by the teacher according to the alleged perturbations and by the feedback principle, as well as by the student. This article reveals the proposed model, which is complemented by recommendations for the organization of self-educational activities at the empirical, theoretical and practical stages of mastering educational material. Pedagogical management of self-education on the basis of this model takes place in four stages: preparatory, organizational, activity, analytical. And also among the most important requirements that ensure effective pedagogical control of self-educational activities of students, its objectivity, consistency, complexity, continuity, manufacturability.